2009
DOI: 10.1177/156482650903000206
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Estimates of Iron Bioavailability in Some Kenyan Complementary Foods

Abstract: Background. Iron-deficiency

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The in vitro digestion/Caco-2 cell culture model was used to evaluate Fe bioavailability from the tested diets by measuring ferritin in the cells (i.e., a measure of cell Fe uptake) following exposure to digests of the samples [4,11,15,16,17,18,20,21,34,52,55,59,60,61,62,66,69,70,71,82,84]. The results showed that in the red mottled beans study [11], ferritin concentrations were significantly higher ( p < 0.05) in cells exposed to the biofortified bean based diet vs. the standard bean based diet, as well as being higher in cells exposed to the Fe biofortified beans vs. the standard beans only ( n = 6, Table 5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The in vitro digestion/Caco-2 cell culture model was used to evaluate Fe bioavailability from the tested diets by measuring ferritin in the cells (i.e., a measure of cell Fe uptake) following exposure to digests of the samples [4,11,15,16,17,18,20,21,34,52,55,59,60,61,62,66,69,70,71,82,84]. The results showed that in the red mottled beans study [11], ferritin concentrations were significantly higher ( p < 0.05) in cells exposed to the biofortified bean based diet vs. the standard bean based diet, as well as being higher in cells exposed to the Fe biofortified beans vs. the standard beans only ( n = 6, Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…As evident in the literature, this model appears to be the most widely applied in vitro model in the field of Fe availability. It is a robust model as it has demonstrated the capability to examine a broad range of foods and meal conditions, and produces results that consistently agree with human studies, and also can investigate interactions and factors related to Fe bioavailability in foods [14,15,16,17,18,34,59,60,61,62,63,64,65,66]. …”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…There is support for this in the research literature. In an in vitro study conducted by Lung’aho & Glahn (2009), the trend of data suggested that the addition of sweet potato (cultivar not specified) to food mixes potentiated iron bioavailability from household-level recipes [17], and a review suggested that sweet potato, particularly the OFSP food matrix, would be expected to promote iron absorption [18]. …”
Section: Introductionmentioning
confidence: 99%